Players’ physical performance in LaLiga when the competition resumes after COVID-19: insights from previous seasons - de Souza, Diego Brito; González-García, Jaime; López-Del Campo, Roberto; Resta, Ricardo; Martínez Buldú, Javier; Wilk, Michal; Coso, Juan (Biology of Sport, 2021)
Due to the COVID-19 outbreak, professional football players competing in LaLiga were confined at home for ~8 weeks and then they were allowed to train to prepare the first competitive match for 4 weeks. As the duration of summer break in the prior four seasons of LaLiga (from 2015-2016 to 2018-2019) was of similar length to the suspension of the championship due to COVID-19 (~12 weeks), we have analysed the running performance of teams competing in LaLiga in these four seasons to anticipate players’ physical performance after the resumption of the competition. The analysis includes the average running distance per game for each of the 38 matchdays that compose LaLiga. One-way ANOVA revealed that there was a main effect of the matchday on total running distance per match (p = 0.001), and in the distance covered between 14.0 and 20.9 km/h (p < 0.001), between 21.0 and 23.9 km/h (p < 0.001) and at above 24.0 km/h (p < 0.001). Overall, the post-hoc analysis revealed that the running patterns progressively increased during the first 8-10 matchdays and then reached a plateau which was significantly different to matchday-1 (p < 0.05). This analysis reveals that, in the prior four competitive seasons of LaLiga, players’ physical performance was lower at the beginning of the season and the teams needed approximately 8-10 matchdays to reach a steady state running performance. These data suggest that football players will progressively increase their performance across the 11 matchdays remaining to complete LaLiga.